2016
DOI: 10.1080/07853890.2016.1252055
|View full text |Cite
|
Sign up to set email alerts
|

Markers of atherosclerosis in patients with Cushing’s syndrome: a meta-analysis of literature studies

Abstract: CS is significantly associated with markers of subclinical atherosclerosis and CV risk. These findings could help establish more specific CV prevention strategies in this clinical setting. Key messages A series of studies reported an increased cardiovascular risk in patients with Cushing's syndrome (CS). In the present meta-analysis we demonstrated that CS is associated with an increased intima-media thickness, higher prevalence of carotid plaques, and lower flow-mediated dilation as compared with controls. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…As expected, ACS presented various cardiometabolic comorbidities, while both ACS and RCS presented, as compared to matched CTR, increased inflammatory parameters such as hs‐CRP, fibrinogen and an increased WHR . Interestingly, platelet number was increased only in ACS, while in RCS, platelet number correlated with sVCAM‐1.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…As expected, ACS presented various cardiometabolic comorbidities, while both ACS and RCS presented, as compared to matched CTR, increased inflammatory parameters such as hs‐CRP, fibrinogen and an increased WHR . Interestingly, platelet number was increased only in ACS, while in RCS, platelet number correlated with sVCAM‐1.…”
Section: Discussionsupporting
confidence: 63%
“…Several studies have demonstrated that remission of CS is associated with a significant improvement of metabolic parameters, although recovery is incomplete in the vast majority of cases, maintaining an increased cardiovascular risk . The mechanisms implicated are unclear and might involve vascular and circulatory factors due to the nonphysiological adrenal replacement therapy, another hormonal deficiency (growth or sexual hormones) and the persistence of increased visceral adipose tissue with deleterious cytokine secretion, maintaining an inflammatory and prothrombotic state and metabolic syndrome‐like features …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, cardiovascular remodelling may be one of the permanent sequelae of long‐standing CS and underscores the importance of early detection and treatment in children . A recent meta‐analysis of 14 studies of atherosclerosis in adult patients with CS showed that CS is significantly associated with subclinical markers of atherosclerosis and cardiovascular risk …”
Section: Introductionmentioning
confidence: 99%
“…An excess of cortisol is also linked to vascular damage, which may lead to cardiovascular complications in CS patients . It has been shown that adult patients with CS have significantly increased carotid intima‐media thickness and a higher incidence of well‐defined plaque walls than control populations with the same cardiovascular risk factors . Furthermore, adult patients with CS had increased left and right ventricular hypertrophy, and lower left atrial ejection fractions and increased end‐diastolic left ventricular segmental thickness compared to the normal population .…”
Section: Introductionmentioning
confidence: 99%